Dengue in the South-eastern region of Brazil: historical analysis and epidemiology Dengue na região sudeste do Brasil: análise histórica e soroepidemiológica - José Carlos Serufo; Andréa Marcia Souza; Valéria Aparecida Tavares; Marcos Cézar Jammal; Josimar Gerônimo Silva (Revista de Saúde Pública, 1993)
The aim of the study is an historical analysis of the work undertaken by the Public Health organizations dedicated to the combat of the Aedes aegypti, as well as an epidemiolocal study of persons with unexplained fever, with a view to evaluating the ocurrence of dengue within the population. The Mac-Elisa, Gac-Elisa, hemaglutination inhibition, isolation and typage tests were used. Organophosphate intoxication in agricultural workers was also assessed by measuring concentrations of serie cholinesterase. A sera samples of 2,094 were collected in 23 towns, and the type 1 dengue virus was detected in 17 towns and autochthony was confirmed in 12 of them. The cholinesterase was measured in 2,391 sera samples of which 53 cases had abnormal levels. Poisoning was confirmed in 3 cases. Results reveal an epidemic the gravity of which was not officially know. The relationshipe between levels of IgM and IgG antibodies indicates the outbreak tendency. The widespread distribution of the vector is troubling because of the possibility of the urbanization of wild yellow fever, whereas the absence of A. aegypti in 2 towns with autochthony suggests the existence of another vector. Since there is no vaccine against dengue, the combat of the vector is the most efficient measure for preventing outbreaks. The eradication of the vector depends on government decisions which depend, for their execution, on the organization of the Health System and the propagation of information concerning the prevention of the disease using all possible means because short and long term results depend on the education and the active participation of the entire population. Objetivou-se fazer análise histórica da atuação dos órgãos de saúde no combate ao Aedes aegypti e realizar estudo soroepidemiológico de pessoas com quadro febril não identificado para avaliar a ocorrência de dengue na população do Estado de Minas Gerais, Brasil. Foram utilizados os testes de Mac-Elisa, Gac-Elisa, inibição da hemaglutinação, isolamento e tipagem. Foram avaliados os níveis de intoxicação de trabalhadores por inseticidas organofosforado, através de dosagem da colinesterase. Foram coletados 1.989 soros de pessoas com quadro febril não identificado em 28 municípios, sendo constatada a ocorrência de dengue em 17 e comprovada autoctonia em 14 municípios. Foi isolado sorotipo 1. A dosagem de colinesterase de 2.391 soros mostrou 53 casos com alterações, sendo comprovados 3 casos de intoxicação. Os resultados mostraram uma epidemia de proporções maiores do que a oficialmente conhecida. A distribuição ampla do vetor traz inquietação quanto à possibilidade de reurbanização da febre amarela silvestre, enquanto a não detecção do A. aegypti em 2 municípios com autoctonia levanta a possibilidade do envolvimento de outros vetores. Como não existe ainda vacina contra o dengue, o combate ao vetor é a medida eficaz na prevenção de surtos. A erradicação do vetor depende de decisão governamental que envolva a organização do sistema de saúde e a participação de todos os meios e formas de repasse de informação, uma vez que o resultado a médio e longo prazo depende especialmente da capacitação popular e sua participação ostensiva.